Study of awareness of diabetes mellitus among diabetics and non-diabetics and drug utilisation pattern in diabetics attending tertiary care general hospital in India - Kumar, Pojala; K., Ravi Shankar; K., Krishnakanth; Alla, Jagadeesh (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Diabetes Mellitus (DM) is one of the most challenging public health problems. It is important to know about the awareness level of a disease condition in a population, which plays a vital role in future development, early detection and prevention of disease. Methods: A total of 200 subjects were interviewed and their details were noted in a specially designed data collection form. The questionnaire contained a series of questions related to demographic characteristics and awareness of DM including general knowledge, risk factors and complications of diabetic and non-diabetic patients. Results: Among 150 subjects were diabetic and 50 were non-diabetic. 60 (40%), 14(28%) of diabetics and non- diabetics were between the age of 41-50. 101 (67.3%) were male, 49 (32.6%) were female. 101 (67.3%) of the study participant had family history of diabetes in diabetic. 45 (44.5%) diabetic, 20 (40.81%) non-diabetic male knows the risk factor for diabetes mellitus and 35 (34.6%), 21 (42.8%) were aware of symptoms, 09(8.9%), 03(6.1%) awareness on complication of diabetes. 21 (20.7%), 06 (12.2%) doesn’t know about Risk factors. Conclusions: The present study conclude a current situation of knowledge and awareness of diabetes mellitus and also emphasizes the need for improvement in knowledge and awareness on diabetes mellitus among the diabetic as well as non-diabetic subjects in order to achieve prevention and better control of diabetes risk factors, complications and its management.